Iran and the First World War : battleground of the great powers - Atabaki, Touraj (Library of modern Middle East studies, 2006)
The First World War, leading to the overthrow of the Qajar regime and replacement by Reza Shah, was pivotal in the history of modern Iran. The Constitutional Revolution of 1906-09 aimed to abolish the arbitrary regime and bring in a modern constitution and parliament. But growing provincial unrest and rebellion by nomadic peoples brought chaos and instability, heightened by the strains of war and intervention by foreign powers. Iran was on the brink of disintegration, modernisation had failed, and growing frustration and pressure from the disillusioned middle classes, intelligentsia and urban population, set the stage for centralisation of power under the Man of Order - Reza Shah.